PREVALENCE OF SILENT MYOCARDIAL INFARCTION IN TYPE 2 DIABETES: INSIGHTS FROM A PRIMARY HEALTHCARE CENTER - Dr. Subhash Chandra (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Introduction: Silent myocardial infarction (SMI) is a significant concern in Type 2 Diabetes Mellitus (T2DM) patients, often leading to delayed diagnosis and poorer outcomes. This study aimed to determine the prevalence of SMI in T2DM patients attending a primary healthcare center and identify associated risk factors. Methods: This cross-sectional study included 320 asymptomatic T2DM patients. Participants underwent clinical assessment, laboratory tests including high-sensitivity cardiac troponin T (hs-cTnT), and 12-lead electrocardiography. SMI was defined as pathological Q waves or significant ST-T wave changes on ECG without a history of cardiac symptoms. Results: The prevalence of SMI was 20.9% (95% CI: 16.7% - 25.8%). Patients with SMI were older (62.7 vs. 57.2 years, p<0.001), had longer diabetes duration (11.2 vs. 7.8 years, p<0.001), and higher HbA1c levels (8.4% vs. 7.6%, p<0.001). Multivariate analysis identified age (OR 1.42 per 10-year increase, p<0.001), diabetes duration (OR 1.28 per 5 years, p=0.003), HbA1c (OR 1.23 per 1% increase, p=0.011), hypertension (OR 1.76, p=0.010), LDL cholesterol (OR 1.09 per 10 mg/dL, p=0.013), and hs-cTnT >14 ng/L (OR 2.87, p<0.001) as independent predictors of SMI. Conclusion: This study reveals a high prevalence of SMI in T2DM patients in primary care, emphasizing the need for cardiovascular risk assessment even in asymptomatic individuals. The identified risk factors, particularly elevated hs-cTnT, could guide targeted screening strategies. Future research should focus on long-term outcomes and the impact of early intervention in this high-risk population.